1999
DOI: 10.1046/j.1523-1739.1999.97513.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ecosystem Features for Conservation: Standing Crops in the Florida Everglades

Abstract: The Everglades in southern Florida, U.S.A., is a major focus of conservation activities. The freshwater wetlands of the Everglades do not have high species richness, and no species of threatened aquatic animals or plants live there. We have, however, identified a distinctive ecological feature of the Everglades that is threatened by canal construction, draining, and nutrient enrichment from agricultural runoff. Compared to values reported from other freshwater systems, standing stocks of periphyton in relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 51 publications
1
87
1
Order By: Relevance
“…Urban and Koebel (1992) used litter bags in dense stands of vegetation to conclude that samples at a eutrophic site had greater abundance of Oligochaeta and Chironomidae but depressed abundance of other taxa relative to an oligotrophic site in WCA-2A. Alternatively, Turner et al (1999) found no effect of enrichment on large-invertebrate biomass, although they used throw traps that primarily collected decapods. Aside from differences in collection techniques among these studies, we suspect that differences in vegetation were primarily responsible for their results.…”
Section: Discussion Standing Stocks and Trophic Levelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Urban and Koebel (1992) used litter bags in dense stands of vegetation to conclude that samples at a eutrophic site had greater abundance of Oligochaeta and Chironomidae but depressed abundance of other taxa relative to an oligotrophic site in WCA-2A. Alternatively, Turner et al (1999) found no effect of enrichment on large-invertebrate biomass, although they used throw traps that primarily collected decapods. Aside from differences in collection techniques among these studies, we suspect that differences in vegetation were primarily responsible for their results.…”
Section: Discussion Standing Stocks and Trophic Levelsmentioning
confidence: 99%
“…This is partially supported by the work of Jordan (1996) in WCA-1, where he illustrated the importance of high habitat complexity to most of the small fish assemblage of the Everglades. However, Jordan (1996) as well as Turner et al (1999) found that small fish densities were as much as 5 times greater in nutrient-rich cattail stands than in any habitat in the oligotrophic interior marsh. Turner et al (1999) hypothesized that increases in productivity cascaded up through the food chain and accumulated as high standing crops of small fishes and consequently, as predicted by food web theory (e.g., Oksanen etal.…”
Section: Discussion Standing Stocks and Trophic Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the coastal Everglades, there is an assemblage of multiple, distinct aquatic habitats including sloughs, creeks, rivers, shallow bays with mangrove islands, and coastal oceans. Urbanization of the surrounding land and global climate change have reduced freshwater flow in volume and duration, thus changing patterns of dissolved oxygen, salinity, primary production, and consequently the distribution of many species of consumers (e.g., Turner et al 1999, Chick et al 2004, Rehage and Trexler 2006. Diminished freshwater flow that has resulted from anthropogenic activities has reduced fish populations, and in turn, limited populations of some upper trophic level predators (e.g., wading birds) though decreased food availability Serafy 2006, Trexler andGoss 2009).…”
Section: Introductionmentioning
confidence: 99%